MENINGKATKAN EKSISTENSI PERKEMBANGAN PENDIDIKAN DAN DINAMIKA PERUBAHAN MASYARAKAT DI DESA SINGAMERTA KELURAHAN KAMANISAN KECAMATAN CURUG - Sri Ndaru Arthawati; Sri Mukti Wirawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
Education is a guideline in facing an era that is always developing with its progress. Concern for education is an important thing that must be considered and implemented based on the results of observations and data collection that have been carried out. Based on the results of observations and data collection, it was found that the Singamerta Village community lacked concern for the world of education. This can be seen from the large number of school children who do not continue their education to a higher level, and the lack of motivation of parents to send their children to school.